German Online Learning with 6c Implementation Strategy in Society 5.0 Era: Opening Opportunities for 21st Century Education - Alida, Erin; Asmorodina, Ibrahim; Aini, Desti Nur (Nexus Publishing NXP, 2024)
Online learning has become an integral part of education, especially foreign language learning since the COVID-19 pandemic. To answer the demands of 21st century education, the right implementation strategy is essential. Among the noteworthy approaches is applying the 6C concept, namely collaboration, communication, critical, creative, character, and empowerment in online learning. In the realm of German language learning, the utilisation of the 6C concept greatly supports the development of competencies necessary for learners to succeed in the modern era. This research uses qualitative approach with descriptive research type. The research findings show that online learning has both positive and negative impacts on the learning process of German language and students' character development through the utilisation of the 6C concept. With the utilisation of the 6C concept in language teaching in the 21st century, it can be expected that the emergence of humanist aspects in education, such as value- and character-centred education and curriculum, which no longer focuses only on mastering subject matter.